Plates theories and applications - Bhaskar, K.; Varadan, T. K. (Switzerland Springer, 2021)
This book covers the essentials of developments in the area of plate structures and presents them so that the readers can obtain a quick understanding and overview of the subject. Several theoretical models are employed for their analysis and design starting from the classical thin plate theory to alternatives obtained by incorporation of appropriate complicating effects or by using fundamentally different assumptions. The book includes pedagogical features like end-of-chapter exercises and worked examples to help students in self-learning. The book is extremely useful for the senior undergraduate and postgraduate students of aerospace engineering and mechanical engineering.
Electronic reproduction
Keywords: Plates (Engineering)